Shared CSF Biomarker Profile in Idiopathic Normal Pressure Hydrocephalus and Subcortical Small Vessel Disease - Jeppsson, Anna; Bjerke, Maria; Hellström, Per; Blennow, Kaj; Zetterberg, Henrik; Kettunen, Petronella; Wikkelsø, Carsten; Wallin, Anders; Tullberg, Mats (Frontiers in Neurology, 2022)
Introduction: In this study, we examine similarities and differences between 52 patients with idiopathic normal pressure hydrocephalus (iNPH) and 17 with subcortical small vessel disease (SSVD), in comparison to 28 healthy controls (HC) by a panel of CSF biomarkers. Methods: We analyzed soluble amyloid precursor protein alpha (sAPPα) and beta (sAPPβ), Aβ isoform -38, -40 and -42, neurofilament light protein (NFL), glial fibrillary acidic protein (GFAP), myelin basic protein (MBP), matrix metalloproteinases (MMP-1, -2, -3, -9, and -10) and tissue inhibitors of metalloproteinase 1 (TIMP1). Radiological signs of white matter damage were scored using the age-related white matter changes scale. Results: All amyloid fragments were reduced in iNPH and SSVD (p < 0.05), although more in iNPH. INPH and SSVD showed comparable elevations of NFL, MBP and GFAP (p < 0.05). MMPs were similar in all three groups except for MMP-10, which was elevated in iNPH and SSVD. iNPH patients had larger ventricles and less white matter changes than patients with SSVD. Conclusion: The results indicates that patients with iNPH and SSVD share common features of subcortical neuronal degeneration, demyelination and astrogliosis. The reduction in all APP-derived proteins characterizing iNPH patients is also present, indicating that SSVD encompass similar pathophysiological phenomena as iNPH.